-3x-12=4x+16

Simple and best practice solution for -3x-12=4x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-12=4x+16 equation:


Simplifying
-3x + -12 = 4x + 16

Reorder the terms:
-12 + -3x = 4x + 16

Reorder the terms:
-12 + -3x = 16 + 4x

Solving
-12 + -3x = 16 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-12 + -3x + -4x = 16 + 4x + -4x

Combine like terms: -3x + -4x = -7x
-12 + -7x = 16 + 4x + -4x

Combine like terms: 4x + -4x = 0
-12 + -7x = 16 + 0
-12 + -7x = 16

Add '12' to each side of the equation.
-12 + 12 + -7x = 16 + 12

Combine like terms: -12 + 12 = 0
0 + -7x = 16 + 12
-7x = 16 + 12

Combine like terms: 16 + 12 = 28
-7x = 28

Divide each side by '-7'.
x = -4

Simplifying
x = -4

See similar equations:

| -18+4x=-2x | | -8x-9=39 | | -8x-9=29 | | y^2-4x^4=0 | | 6e^4x+13e^2x=28 | | -4y+1=2 | | B/7-11=7 | | 12+13=7x-7 | | -15=c-15 | | 8(-13)-3(-13-5)=4(-13)+4(-13+6) | | 2y-4=3y-9 | | 8-2b=-2/3(12b+6) | | y=+25 | | 13/15(x-3y-5z) | | 2(z-1)/2z-3-3(z+2)/2z-3-z-1/3-2z | | 1.72g-9=0.46 | | x^2-(5-i)x+6=0 | | 28=k+14 | | 2x+9x=-5 | | 5/7d=45 | | 1/8/1/3(2)=x | | 3+8x-6=6x+7 | | C/-10=-5 | | 5a+4b=20 | | 2Xsquared+9X=-5 | | 48-x+22+2-x= | | 4a=0.36 | | −3y+7+1 | | 5x+2x-4=38 | | 2(2x+3)-2=4(x+1) | | -18x+2=3x | | 2(4x-6)-8=8x-20 |

Equations solver categories